PENGARUH PERSON-ORGANIZATION FIT, BEBAN KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PERAWAT (Studi pada Perawat Rumah Sakit Ken Saras Kabupaten Semarang) - Nugroho, Septian; Rahardja, Edy (Diponegoro Journal of Management, 2018)
The problem that arises in Ken Saras Hospital is a decrease in employee performance which can be seen from the decline in the employee performance index and supported by the results of a survey which states that patients are less satisfied with the services of employees. Variables suspected of influencing employee performance are person-organization fit, workload and transformational leadership. This study aims to analyze the influence of person-organization fit, workload and transformational leadership on the performance of nurses at Ken Saras Hospital.The population and sample used in this study were nurses at Ken Saras Hospital. The sampling technique used is the census. Data collection methods in this study use questionnaires and interviews. Data analysis method uses multiple linear regression analysis.Based on the results of the study, person-organization fit, and transformational leadership have a positive effect on the performance of nurses at Ken Saras Hospital, while the workload has a negative effect on the performance of nurses at Ken Saras Hospital. Employee performance can be explained by the independent variable, person-organization fit, workload and transformational leadership, amounting to 82.2%.